Pursuer Navigation Based on Proportional Navigation and Optimal Information Fusion. (21st October 2021) - Feng, Shulin; Li, Zhanxin; Liu, Li; Yang, Hongyong; Yang, Yuanhua; Lv, Gaohuan; Yang, Liang
Abstract : Pursuer navigation is proposed based on the three-dimensional proportional navigation law, and this method presents a family of navigation laws resulting in a rich behavior for different parameters. Firstly, the kinematics model for the pursuer and the target is established. Secondly, the proportional navigation law is deduced through the kinematics model. Based on point-to-point navigation, obstacle avoidance is implemented by adjusting the control parameters, and the combination can enrich the application range of obstacle avoidance and guidance laws. Thirdly, information fusion weighted by diagonal matrices is used for decreasing the tracking precision. Finally, simulations are conducted in the MATLAB environment. Simulation results verify the availability of the proposed navigation law.